Analytical method for 44 pesticide residues in spinach using multi‐plug‐filtration cleanup based on multiwalled carbon nanotubes with liquid chromatography and tandem mass spectrometry detection. Issue 9 (13th April 2016) - Qin, Yuhong; Huang, Baoyong; Zhang, Jingru; Han, Yongtao; Li, Yanjie; Zou, Nan; Yang, Jianguo; Pan, Canping
Abstract : Spinach is one of the most commonly planted vegetables worldwide. A high chlorophyll content makes spinach a complicated matrix in pesticide residue analysis. In this study, a rapid clean‐up method was developed for the analysis of pesticide multi‐residues in spinach followed by liquid chromatography with tandem mass spectrometry. A modified QuEChERS method with multiwalled carbon nanotubes and carbon material was adopted in the multi‐Plug Filtration Cleanup procedure. This method was validated for 44 representative pesticides spiked at two concentration levels of 10 and 100 μg/kg. The pesticides of different physicochemical properties were registered on spinach in China. The recoveries were between 76 and 114% for major pesticides with relative standard deviations of less than 15%, except for quizalofop‐P‐ethyl, pyrimethanil, and carbendazim. Matrix‐matched calibration curves were performed with the coefficients of determination higher than 0.995 for the studied pesticides for concentration levels of 10–500 μg/kg. The limits of quantitation ranged from 2 to 10 μg/kg. The developed method was successfully applied to determine pesticide residues in Chinese market spinach samples.